Harmonious intervention China's quest for relational security - Huang, Chiung-Chiu (Rethinking Asia and international relations, 2014)
Two major features of international relations at the beginning of the 21st century are global governance and an ascendant China. Whether or not China will ultimately sinicize global governance or become assimilated into global norms remains both a theoretical and a practical challenge.